2019
DOI: 10.3389/fonc.2019.01066
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Key Immune Checkpoint Receptors on Tumor-Infiltrating T Cells From Multiple Types of Cancer

Abstract: Background: Cancer patients often display dysfunctional antitumor T-cell responses. Because noteworthy benefits of immune checkpoint pathway blockade, such as programmed cell death protein 1 (PD-1) inhibitors, have been achieved in multiple advanced cancers, the next critical question is which mono-blockade or combinatorial blockade regimens may reinvigorate antitumor T-cell immunity in those cancer patients while limiting immune-related adverse effects.Method: This study recruited, in total, 172 primary cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 72 publications
(65 reference statements)
3
49
0
Order By: Relevance
“…We observed the complex network among immune checkpoint molecules, as many of them correlate to other immune checkpoint proteins. This can reflect previous observations that these proteins are frequently co-expressed on multiple cell types, including T cells, antigen-presenting cell, and/or malignant cells 47 . We also observed that several immune checkpoint proteins positively correlate to genital inflammation, which was highly elevated in cancer patients compared with other groups 18 .…”
Section: Discussionsupporting
confidence: 88%
“…We observed the complex network among immune checkpoint molecules, as many of them correlate to other immune checkpoint proteins. This can reflect previous observations that these proteins are frequently co-expressed on multiple cell types, including T cells, antigen-presenting cell, and/or malignant cells 47 . We also observed that several immune checkpoint proteins positively correlate to genital inflammation, which was highly elevated in cancer patients compared with other groups 18 .…”
Section: Discussionsupporting
confidence: 88%
“…77 A recent study in our group has shown that the expression of BTLA, TIGIT, KLRG-1, and 2B4 is not enriched on TILs compared with their counterparts in peripheral blood of cancer patients. 78 Most importantly, we found that co-expression of specific IRs including Tim3 and PD-1 is highly prevalent on CD8 + TILs across different cancer types, such as in lung, kidney, and breast cancers. This suggests that certain IRs are likely more favored in the tumor microenvironment to suppress antitumor CTLs responses.…”
Section: Exhausted T Cells Exhibit Elevated Inhibitory Receptor Exprementioning
confidence: 71%
“…Among them, CD27 and CCR7 were markers of T cell differentiation. Previous studies showed that advanced CD27 − CCR7 − CD45RA − T cell of PD-1 + TIGIT + 2B4 + Tim-3 + KLRG-1 − CTLA-4 − CD8 TILs was related to poorly differentiated cervical cancer (37), and CCR7 might be associated with lymph node metastasis. So that they could be used as a prognostic factor for survival (38).…”
Section: Discussionmentioning
confidence: 95%